Molecular dynamics simulation of nanocrack closure mechanism and interface behaviors of polycrystalline austenitic steel - Chen, Huiqin; He, Sizhe; Chen, Juan; Chen, Fei; Zhang, Sairu; Zhang, Yingfan (Frontiers in Materials, 2022)
Void-type defects in heavy forgings deteriorate the mechanical properties and service life. In this work, the evolutions of a precrack closure and healing and mechanical properties of FeCrNi polycrystalline samples are performed under different loading conditions by using molecular dynamics simulation. The stress-strain curves show that the sample with interface exhibits higher Young's modulus and yield strength than those with crack despite the loading conditions. These results imply that the samples under compression loading have a higher ability to resist plasticity while the shear stress facilitates plastic flow. The crack closure and healing happen under compression stress by dislocation dominant plastic deformation, while the crack length shrinks and the crack tips expand along GBs and interface because of its higher stress under shear loading. The dislocation activities, including dislocation emission, slip and interactions with cracks, grain boundaries and dislocations, contribute to the plasticity of the specimen under compressive loading. In addition to dislocation activities, grain boundary slip, grain rotation and twinning are potential plastic deformation mechanisms under shear loading.